Emergence of ST39 carbapenem-resistant Klebsiella pneumoniae producing VIM-1 and KPC-2. (January 2022) - Karampatakis, Theodoros; Zarras, Charalampos; Pappa, Styliani; Vagdatli, Eleni; Iosifidis, Elias; Roilides, Emmanuel; Papa, Anna
Abstract: Introduction: Carbapenem-resistant Klebsiella pneumoniae (CRKP) causes life-threatening hospital-acquired infections. KPC and VIM carbapenemase production is the main molecular mechanism for carbapenem resistance. The aim of the current study was the genetic characterization of four ST39 CRKP isolates simultaneously producing VIM-1 and KPC-2, obtained in a Greek tertiary hospital. Methods: Identification and antimicrobial susceptibility testing were performed through VITEK 2. Multiplex PCR, multiplex lateral flow immunoassay, phenotypic tests and next generation sequencing were applied. The sequence reads were de novo assembled and annotated, while antimicrobial resistance genes and plasmids were identified using bioinformatics software. Genomic comparison and core genome single-nucleotide polymorphism-based phylogenetic analysis were also performed. Results: Three isolates were pandrug-resistant, and one was extensively drug-resistant; they all carried bla VIM-1 and bla KPC-2 genes and were assigned to ST39. Bla VIM-1 was integrated in a class 1 integron. They all harboured many antimicrobial resistance genes and various plasmids. The mgr B gene of all isolates was disrupted by an insertion sequence (ISKpn14). Genome comparison and phylogenetic analysis revealed that the isolates were closely related. Conclusion: To our knowledge this is the first report on detection of CRKP ST39 isolates simultaneously producing VIM-1 and KPC-2 in addition to colistin resistance. The knowledge of the clonal relatedness of the isolates can lead to the implementation of strict infection control measures absolutely needed to eliminate their spread. Highlights: The genetic characterization of four ST39 CRKP isolates was performed. All ST39 CRKP isolates carried blaKPC-2 and blaVIM-1 genes. All isolates were closely related with each other implying clonal dispersion.